Numerical Simulation of Temperature Deformation for Radio Frequency Ion Thruster Electrodes. (2017) - Fedorov, V.A.; Mogulkin, A.I.; Obukhov, V.A.; Abgaryan, V.K.; Balashov, V.V.
Abstract: An ion-extraction system (ISE) assembly is the most complicated unit of an ion thruster (IT). The IES electrodes made as thin-walled dished grids are subject to non-uniform radial heating. This is accompanied by grid deformation. An IES assembly should provide the stability of the interelectrode gap with strict tolerances. To investigate the influence of the grid form (a value of initial deflection) on the thermal deformation (thermal deflection) the behavior of a screen (SG) and accelerated (AG) dished grids has been simulated for different compatible materials and geometry as follow: SG: thickness is 0.3-0.7 mm; diameter is 160 and 450 mm for molybdenum alloy, titanium alloy, carbon-carbon composite materials; AG: thickness is 1.0-2.5 mm; diameter is 160 and 450 mm for titanium alloy, carbon-carbon composite materials. ANSYS software has been used for numerical analysis. For every combinations of materials and geometries there has been an initial form providing the thermal deformation in the ordered limits. The results of ANSYS analysis are compared with the dates received by a simplified algorithm giving a significant saving of time for calculation.